Experience with the redo pull-through for hirschsprung's disease - Devendra K Gupta; Kashish Khanna; Shilpa Sharma (Wolters Kluwer Medknow Publications, 2019)
Aim: This study aims to evaluate the need of Redo pull-through (Re PT) procedures for Hirschsprung's disease (HD) and suggest preventive strategies. Materials and Methods: Patients who underwent redo procedures for HD from 1980 to 2016 by a single surgeon were retrospectively reviewed. Results: Of 167 patients operated for HD, 32 underwent Re PT; 7 were previously operated by the same surgeon, while 25 were referred from outside. Indication for Re PT included residual disease including the rectal pouch following-Duhamel (12), false-negative biopsy (3), retraction of bowel (5), anorectal stricture (2), bowel twist (1), cuff inversion (2), postmyectomy continued symptoms after primary PT (1), fecal fistula (1), Re PT after surgery for adhesive intestinal obstruction (3), bleeding (1), and combination of causes, including scarred perineum (1). Age at follow-up ranged from 2.5 to 26 years. Proximal diversion was performed in 19 and 14 underwent open Scott Boley's/Soave PT and 5 ileoanal anastomosis. Of the remaining, nondiverted 13 patients, 5 underwent transanal endorectal PT and 8 underwent PT of colostomy. Conclusions: Most patients of Re PT came after an initial Duhamel's procedure. Retraction of bowel, inversion of cuff, twist, distal bowel stricture, and perianal fibrosis were found after Scott Boley procedure. Proper planning with an initial diversion, nutritional buildup, barium study evaluation, frozen section facility, experienced pathologist, and an expert surgeon are prerequisites for a successful outcome after an initial as well as Re PT.